Oligonucleotide-directed triple helix formation at adjacent oligopurine and oligopyrimidine DNA tracts by alternate strand recognition. - Jayasena, S D (1992)
A significant limitation to the practical application of triplex DNA is its requirement for oligopurine tracts in target DNA sequences. The repertoire of triplex-forming sequences can potentially be expanded to adjacent blocks of purines and pyrimidines by allowing the third strand to pair with purines on alternate strands, while maintaining the required strand polarities by combining the two major classes of base triplets, Py.PuPy and Pu.PuPy. The formation of triplex DNA in this fashion requires no unusual bases or backbone linkages on the third strand. This approach has previously been demonstrated for target sequences of the type 5'-(Pu)n(Py)n-3' in intramolecular complexes. Using affinity cleaving and DNase I footprinting, we show here that intermolecular triplexes can also be formed at both 5'-(Pu)n(Py)n-3' and 5'-(Py)n(Pu)n-3' target sequences. However, triplex formation at a 5'-(Py)n(Pu)n-3' sequence occurs with lower yield. Triplex formation is disfavored, even at acid pH, when a number of contiguous C+.GC base triplets are required. These results suggest that triplex formation via alternate strand recognition at sequences made up of blocks of purines and pyrimidines may be generally feasible.